Effects of Triptolide on the Expression and Activity of NF-κB in Synovium of Collagen-induced Arthritis Rats - 涂胜豪 胡永红 曾克勤 张明敏 赖先阳 张玮琛 (Journal of Huazhong University of Science and Technology. Medical sciences, 2005)
Summary： The expression and activity of NF-kB in the synovium of collagen-induced arthritis （CIA） rats was detected in order to investigate the possible therapeutic effects of triptolide on rheumatoid arthritis （RA）. The experimental Wistar rat model of CIA was set up by intradermal injection of emulsion of bovine collagen 11 and the successful rate of setting-up models was evaluated by arthritis index （AI）. Rats were grouped randomly into three groups： normal, model and treatment group. The expression of TNF-α and IL-6 in synovial fluid was detected by ELISA, and the expression and activity of NF kB in synovium by immunohistochemistry method and by electrophoretic mobility shift assay （EMSA） respectively. As compared with normal group, the expression of TNF a and IL-6 in synovia （P〈0. 05）, and the expression and activity of NF-kB （P〈0.05） in synovium were increased in model group. There was statistical difference in above-mentioned indexes between model group and treatment group. Triptolide may play a protective role in IRA via downregulating the expression and activity of NF-kB in synovium.